Marketing Management Strategy in Influencing Snack Purchase Decisions by Alpha Generation Parents in Indonesia - Dian Siti Rohmah; Mohamad Rifqy Roosdhani; Anna Widiastuti (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This research analyzes marketing-based strategies for influencing health consciousness in influencing snack purchasing decisions for the Generation Alpha segment, with a focus on optimizing the marketing mix through a mediating role of front-of-pack labeling, nutritional knowledge, and food safety concern. Using a quantitative research methodology with a survey of 150 parents in Indonesia as purchasing decision makers, data analysis was carried out using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) to test mediation models from a marketing management perspective. The findings show that health consciousness significantly affects consumer perception of front-of-pack labeling (β=0.610), nutritional knowledge (β=0.551), and food safety concern (β=0.551). Crucially, food safety concern proved to be a key mediator (β=0.246) in marketing strategy, while front-of-pack labeling was not yet effective as a marketing communication tool in this context. The managerial implications of this study are the need to reformulate the marketing mix with an emphasis on product safety as a competitive advantage, helping snack manufacturers design more effective strategies, and the government in developing informative and positioning labeling policies, with food safety concern as a core value proposition. The originality of this study enriches the Theory of Planned Behavior (TPB) in the context of consumer behavior, developing an integrative marketing model that optimizes health consciousness through a parallel mediation approach, especially in the Alpha Generation segment in developing countries such as Indonesia.